Evaluation of color Stability of Different Restorative Materials Used in Pediatric Dentistry - İpek, İrem; Karaağaç Eskibağlar, Büşra (Selcuk University, 2024)
Background: The aim of this study was to evaluate the color changes of restorative materials (Filtek z550, EverX Posterior, Dyract XP, EQUIA Forte Fill), which are frequently used in pediatric dentistry, after aging with beverages (cola, cherry juice) that children and adolescents frequently consume in their daily life. +,,0 Methods: Four different restorative materials; nanohybrid composite (Filtek z550), glass fiber reinforced bulk fill composite (EverX Posterior), polyacid modified composite resin (Dyract XP) and glass hybrid glass ionomer cement (EQUIA Forte Fill) were used. A total of 120 samples were prepared for each material using plexiglass molds with a thickness of 2 mm and a diameter of 10 mm. A total of 30 samples from each group were divided into 3 group (n=10) to be immersed in cola, cherry juice and distilled water. After the initial color measurements, the samples were stored in beverages for 7th and 14th days. Color change values (?E) were calculated after 7th and 14th days. Results: When the ?E values of materials were examined, it was observed that EQUIA Forte Fill group had the highest color change and Filtek z550 group had the lowest color change. Conclusion: The glass hybrid GIC showed the most distinct color change in all time periods and beverages. ?E values in cola and cherry juice of all resin-based restorative materials tested were less than or equal to 3.3. Therefore, color changes were clinically acceptable as they were not visually perceptible. © 2024, Selcuk University. All rights reserved.
Farklı Restoratif Materyallerin Renk Stabilitesinin Değerlendirilmesi
Keywords: Bulk-Fill Composite Resin; Color Stability; Glass Hybrid Glass Ionomer Cement